1997
DOI: 10.1084/jem.185.12.2171
|View full text |Cite
|
Sign up to set email alerts
|

Eotaxin-2, a Novel CC Chemokine that Is Selective for the Chemokine Receptor CCR3, and Acts Like Eotaxin on Human Eosinophil and Basophil Leukocytes

Abstract: A novel human CC chemokine consisting of 78 amino acids and having a molecular mass of 8,778.3 daltons (VVIPSPCCMF FVSKRIPENR VVSYQLSSRS TCLKAGVIFT TKKGQQ SCGD PKQEWVQRYM KNLDAKQKKA SPRARAVA) was isolated together with three minor COOH-terminally truncated variants with 73, 75, and 76 residues. The new chemokine was termed eotaxin-2 because it is functionally very similar to eotaxin. In terms of structure, however, eotaxin and eotaxin-2 are rather distant, they share only 39% identical amino acids and differ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
292
2
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(302 citation statements)
references
References 33 publications
7
292
2
1
Order By: Relevance
“…A similar reduction was observed in mice deficient in eotaxin [14]. Although less is known about the in vivo role of other CCR3 ligands, such as eotaxin-2 [15], MCP-4 [16], RANTES, and MCP-3 [8], the information accumulated to date indicates that the development of CCR3 receptor antagonists represents a possible approach to blocking pulmonary eosinophilic inflammation, which is characteristic of asthma [17,18]. Toward this end, it is important to understand the pharmacology of interaction of CCR3 with its ligands, such that appropriate assays are used to most readily identify the antagonists.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…A similar reduction was observed in mice deficient in eotaxin [14]. Although less is known about the in vivo role of other CCR3 ligands, such as eotaxin-2 [15], MCP-4 [16], RANTES, and MCP-3 [8], the information accumulated to date indicates that the development of CCR3 receptor antagonists represents a possible approach to blocking pulmonary eosinophilic inflammation, which is characteristic of asthma [17,18]. Toward this end, it is important to understand the pharmacology of interaction of CCR3 with its ligands, such that appropriate assays are used to most readily identify the antagonists.…”
Section: Introductionmentioning
confidence: 53%
“…Toward this end, it is important to understand the pharmacology of interaction of CCR3 with its ligands, such that appropriate assays are used to most readily identify the antagonists. Several chemokines have been described to bind to CCR3 on human eosinophils [7,8,12] and induce chemotaxis in vitro [12,15,16,19,20]. Other measurements of receptor-activated intracellular events such as increases in intracellular calcium levels [7,12,15,16,[20][21][22][23], production of reactive oxygen [15,[21][22][23][24], histamine release [15], and actin polymerization [22][23][24] have also been used to characterize CCR3 ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of Ccl11 typically contributes to the recruitment of Th2 cells that express Ccr3, the chemokine receptor for Ccl11, to the site of inflammation (28,32,34,45). The observation that high levels of pancreatic Ccl11 transcripts are associated with resistance to T1D in BBDP rats led us to determine whether these high levels are also correlated with a Th2 bias in the insulitic lesion of these animals.…”
Section: Increased Levels Of Ccl11 Expression In the Pancreas Are Assmentioning
confidence: 99%
“…The physiological significance of this expression remains elusive, although it has been shown that the interaction of extracellular matrix proteins with b cells results in NF-kB activation and the subsequent synthesis of cytokines by b cells, in vitro (27). Ccl11 is one of the three members of the eotaxin family of C-C chemokines that are potent chemoattractants for Ccr3-expressing cells, which include eosinophils, mast cells, basophils, neutrophils, and Th2 lymphocytes (28)(29)(30)(31)(32)(33)(34). Although the presence of eosinophils and mast cells within the insulitic lesions of BBDP rats has been previously reported (35)(36)(37), the observation that Ccl11 is upregulated in the target organ of this diabetogenic process remains puzzling (24,37), particularly because diabetes in the BBDP rat is a Th1-mediated autoimmune disease (38)(39)(40).…”
mentioning
confidence: 99%
“…However, these proteins are non-selective and stimulate a wide variety of cell types besides eosinophils. More recently, two more "Eotaxins" with high functional similarity, but rather low sequence similarity, when compared with the originally-discovered Eotaxin have been identified (Forssmann et al 1997, Patel et al 1997, White et al 1997, Shinkai et al 1999. To distinguish these three distinct gene products, the names Eotaxin-1 (CCL11, formerly Eotaxin), Eotaxin-2 (CCL24) and Eotaxin-3 (CCL26) are used (Zlotnik et al 2000).…”
Section: Chemokines As Chemoattractants For Eosinophilsmentioning
confidence: 99%